The suitability of the CISG and OHADA for small and medium-sized enterprises engaging in international trade in West and Central Africa - Donfack, Narcisse Gaetan Zebaze (University of South Africa, 2015)
It is universally acknowledged that international trade and cooperation have become key drivers of SMEs. Indeed, the success of SMEs in the sales sector depends upon their capacity to conquer the foreign market and compete with larger companies. Many SMEs today, in particular those in Central and West Africa, are very much aware of this reality. However, because of differences between domestic laws and their maladjustment, many African SMEs still struggle to enter the international market and compete with larger companies. It is therefore obvious that any SMEs that want to succeed in international commerce today will be called upon to confront different regulations, whether domestic, regional or international, which are often shaped according to the realities and expectations of a particular environment. The challenge today is to regulate and harmonise these different legal systems, in order to render the law identical in numerous jurisdictions. This process of unifying the law internationally, in particular the law of sale, started in 1920 and culminated in 1988, with the implementation of the CISG. This Convention, which has become the primary law for international sales contracts, endeavours to deal with this problem of differences in law between states on a global scale, by attempting to achieve a synthesis between different legislations, such as civil law, common law, socialist law, and the law regarding industrialised and Third World countries. Even though the CISG appears to be a compromise between different legal systems, the fact remains that it is not yet applicable in many countries, especially those in Central and West Africa, which are mostly still ruled by domestic and regional law, namely the OHADA. The purpose of this study is to attempt to analyse and compare the OHADA’s Uniform Act Relating to Commercial Law to the CISG, in order to identify similarities and differences between the two, and to determine, with regard to the operating mode and structure of SMEs in West and Central Africa, which one of the two legislations is more appropriate.
Keywords: CISG; Cameroon Civil Code; Cameroon contract law; Comparative law; Formation of a contract; Incoterms; International sales law; Internationalisation; OHADA law; Obligations of the buyer; Obligations of the seller; SMEs; Sales of goods; Termination of a contract

Passivity rule: a comparison between European Union, United States and China - Casamassima, Stefano (LUISS Guido Carli, 2015)
Passivity rule: origin and reasons. Adoption of the European directive 25/2004 and its provisions. The adoption of the European directive by major member states and passivity rule in USA and China. The economic implications of passivity rule. Possible future developments.

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

The potential impact of the Hague principles on choice of law in international commercial contracts in the BRICS countries - Reddi, Saranya (University of Johannesburg, 2015)
LL.M. (International Commercial Law) Please refer to full text to view abstract
Keywords: BRIC countries; Commercial law; Conflict of laws; Contracts (International law)

A comparison of Kenyan and South African law on security by means of movables - Koli, Natasha Mwende (University of South Africa, 2015)
This study compares the legal principles applicable in both South Africa and Kenya in the creation of security by means of movables. It identifies the forms of security that can be created in the two jurisdictions. The main focus will be on the creation, publicity, priority of security interest and enforcement of the said interests. The research will in addition establish the challenges (if any) that are encountered when creating security by means of movables in Kenya and identify practical solutions that can be adopted in order to improve the creation of security by means of movables in Kenya.
Keywords: ACCESS TO FINANCE; Creation of security; Kenyan law; Lenders and security; Movable property; Secured transactions; Security; Security by means of movables; South African law

Cross border insolvency: new trends - Napolitano, Andrea (LUISS Guido Carli, 2015)
The EU regulation no. 1346/2000. The proposal for a modification of the regulation. New trends.

How to copy a song with impunity : a legal perspective on copyright infringement cases for musical works - Rogowski, Adrian (Stellenbosch University, 2015)
Music has, and continues to play, an important role in society. It is therefore natural that more music composers enter the scene to capitalize upon this role that music has in society. It is however becoming more common place for music composers to start copying each other, either directly or indirectly. Fortunately, copyright laws have been developed to further protect the rights enjoyed by copyright holders, such as music composers, and these laws essentially protect the composers from the unlawful reproduction of their original music. Copying is, to some degree, inevitable, therefore, the question asked by this paper is to what extent is someone entitled to ‘copy’ from another person without it amounting to copyright infringement. In determining if there is copyright infringement, two tests must be applied and satisfied, namely, the causal connection test, and the substantial similarity test. Causal connection is usually met by establishing whether the alleged infringer had access to the original work. The substantial similarity test is the focus of this paper. The courts rely on this test to determine if that part which was reproduced from the original work is of substance i.e. if it is a part of the work which attributes uniqueness and quality to the original song. Of course, this test is notoriously difficult to understand and apply, hence the need for this paper to address the question on when there is substantial similarity in two works. This paper is of benefit to academics, authors (musicians) and lawyers, as not only is the substantial similarity test discussed from a theoretical point of view, but the question of when something is substantially similar is answered from a pragmatic point of view. It is hoped that this paper is used as a guideline in understanding and applying the substantial similarity test in music copyright infringement cases.
Keywords: Copyright; Copyright infringement; Music; Musical compositions

Reconsidering Distributions: A Critical Analysis of the Regulation of Distributions to Shareholders in the Companies Act of 2008, with Special Reference to the Solvency and Liquidity Requirement - Van der Merwe, Constant Pieter (Stellenbosch University, 2015)
The Companies Act 71 of 2008 introduces a completely new system for the regulation of distributions by a company to its shareholders. The preferred method for protecting the interests of creditors in distributions is now based on a solvency and liquidity test. Regrettably, the provisions setting out the requirements for distributions on the one hand and the solvency and liquidity test on the other have been poorly drafted. This thesis first explains and then applies an innovative interpretation theory to these provisions with a view to piecing together coherent content. The thesis finds that creative interpretations will not suffice in various places, meaning that substantive revision is required. The thesis concludes with brief amendment proposals and accompanying commentary.
Keywords: Business enterprises; Companies; Companies Act, 2008; Companies régulations; Company insolvency; Company liquidity; Insolvency; Régulations; Shareholders; South Africa

The effectiveness of the e-commerce legal framework in selected African countries - Esanwa, Maryam Adetokunbo (University of KwaZulu-Natal, 2015)
Abstract not available.
Keywords: Africa; E-commerce; Electronic commerce; Information technology

A critical appraisal of the misapplications of black economic empowerment and the common misperceptions that surround it - Govender, Prenisha (University of KwaZulu-Natal, 2015)
Broad-Based Black Economic Empowerment is a regulatory framework, which is unique to South Africa. This dissertation reflects upon the evolution of Broad-Based Black Economic Empowerment programme, from the commencement of apartheid to date. Broad-Based Black Economic Empowerment was implemented by government, with the objective of resolving the injustices created by the apartheid regime. Government seeks to achieve this objective by integrating the historically disadvantaged individuals within South Africa into the mainstream of the economy. However, the reality is that the implementation of the Black Economic Empowerment programme has not been entirely successful. This dissertation is a critical analysis of the application of Broad-Based Black Economic Empowerment and related legislation. It aims to highlight the challenges faced by government in enforcing the Broad-Based Black Economic Empowerment programme, with a particular focus on the following issues: fronting, misrepresentations and common misperceptions. This dissertation begins by reflecting upon the historical context of South Africa toward democratization, secondly it analyses the current applicable legislation and explores the current issues. This research shows that Broad-Based Black Economic Empowerment is essentially a work in progress programme as there is much room for improvement. Scholars have established that companies and other entities regularly circumvent the Act. Furthermore, many individuals misunderstand the programme and its purpose. The research concludes Broad-Based Black Economic Empowerment does have potential for success. In considering the approach taken by Malaysia, it is established that the key to overcome these major issues is education.
Keywords: Affirmative action programs; Blacks Economic conditions; Business enterprises; Employee empowerment

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

A comment on debt relief options for insolvent consumer debtors in South Africa - Xulu, Anele Innocentia Nombuso (University of KwaZulu-Natal, 2015)
The paper will be focused on examining the debt relief options available for consumer debtors in South Africa. This paper will look at the relationship between the National Credit Act 34 of 2005 and the Insolvency Act 24 of 1936. Further, it will examine the relationship between the provisions of section 74 of the Magistrates’ Courts Act 32 of 1944. The paper will conclude by looking at debt relief options available for consumer debtors in the United States of America and in England and Wales and will make comparative comments and recommendations on how we can adopt some provisions into our own insolvency system.
Keywords: Consumer credit; Debt relief; Debtor and creditor; Insolvency; Insolvency Act; National Credit Act; South Africa